CYTOTOXICITY ACTIVITY OF SOME INDIAN MEDICINAL PLANTS - Neerugatti, Dora Babu; Battu, Ganga Rao; Bandla, Raviteja (International Journal of Current Pharmaceutical Research, 2016)
Objective: The current study is carried out to evaluate cytotoxicity activity of the methanolic extracts of some medicinal (Buchanania axillaris Desr, Tamilnadia ulignosa Retz, Phaseolus semierectus L and Stylosanthes fruticosa Retz). Methods: Cytotoxicity activity was evaluated on human cancer cell lines such as lung cancer (A549) and skin cancer (A431) using MTT assay method. Results: The selected plant extracts showed the dose-dependent cytotoxicity activity on the tested cell lines. The cytotoxicity variations on different cell lines were also observed for tested plants extracts. The cytotoxicity of the extracts was increased as the concentration of them was increased. Among all tested plants extracts Phaseolus semierectus showed the better cytotoxicity activity on tested cell lines. Conclusion: The results of the present study supported the folkloric usage of the studied plants and confirmed that the plant's extracts have the bioactive constituents with cytotoxic properties and their isolation can be useful for developing new anticancer drugs.